Clinical features for diagnosis and management of patients with PRDM12 congenital insensitivity to pain. Issue 8 (14th March 2016) - Zhang, Stella; Malik Sharif, Saghira; Chen, Ya-Chun; Valente, Enza-Maria; Ahmed, Mushtaq; Sheridan, Eamonn; Bennett, Christopher; Woods, Geoffrey
Abstract : Background: Congenital insensitivity to pain (CIP) is a rare extreme phenotype characterised by an inability to perceive pain present from birth due to lack of, or malfunction of, nociceptors. PRDM12 has recently been identified as a new gene that can cause CIP. The full phenotype and natural history have not yet been reported. Methods: We have ascertained five adult patients and report their clinical features. Results: Based on our findings, and those of previous patients, we describe the natural history of the PRDM12-CIP disorder, and derive diagnostic and management features to guide the clinical management of patients. Conclusions: PRDM12-CIP is a distinct and diagnosable disorder, and requires specific clinical management to minimise predictable complications.